Seroprevalence of Hepatitis E Virus (HEV) Infection Among Patients Attending BSMMU, Dhaka (Bangladesh Journal of Medical Microbiology, 2016)
The present study was done to determine the seroprevalence of the infection by Hepatitis E virus (HEV) among patients attending Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka. Serum samples from 408 subjects, aged between 0-69 years, attending BSMMU from different rural and urban areas of Bangladesh were tested for HEV IgG by enzyme linked immunosorbent assay (ELISA). Anti-HEV IgG was found among 20.6% of the study population. A higher rate of seropositivity (26.1%) was found among patients attending from urban than those from rural (15.1%) areas which is statistically significant (P < 0.01). A gradual rise in prevalence of anti-HEV IgG was observed among the study population according to age, starting from 10.6% in the 0-9 years age group and increasing with higher age thereafter. The HEV IgG prevalence reached its highest (28.3%) in the 30-39 years, which remained at around the same level in the 40-49 years (25.0%) and 50-59 years (26.0%), with a drop of incidence in the 60-69 years age group (17.8%). The study indicates HEV infection as a public health problem in Bangladesh and suggests to ensure increased awareness to prevent andcontrol future outbreaks.Bangladesh J Med Microbiol 2007; 01 (02): 52-55